PENGARUH KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT. JIMMULYA - Mohd. Kurniawan DP (JURNAL KOMPETITIF, 2018)
The purpose of this study to determine the influence of leadership, motivation and organizational culture on employee work satisfaction PT. Jimmulya. Data analysis techniques used are validity test, reliability test, multiple linear regression, coefficient of determination test, t test and F test using SPSS 17. The results showed that leadership, motivation and organizational culture partially positively and significantly influence on job satisfaction . Simultaneously, leadership and organizational culture have positive and significant effect on job satisfaction with R2 = 0,0,426. This value explains the leadership and organizational culture simultaneously as much as 42.6%. While the rest, 57.4% is explained by variables other than leadership and organizational culture.